"A position of great trust and responsibility" : a social history of the Grahamstown Asylum, 1875 "“ c. 1905 - Van Zyl, Kylie (Rhodes University, Faculty of Humanities, Department of History, 2020)
Much has been written about the inequalities inherent in the psychiatric care provided to mentally ill individuals in the Cape Colony, but to date few works have been produced that describe in detail the processes and care regimes at particular institutions. This thesis examines the history of care and custody provided by the Grahamstown Asylum in the Cape between the years of 1875 and 1905. The intention is to determine the means and methods by which the Asylum's authorities developed, almost unchallenged, a system of unequal treatment and favouritism within that facility, and what this meant for the men and women committed to the Asylum's custody. To this end, contemporaneous official reports from Asylum staff and Colonial authorities were consulted, in conjunction with the Asylum's internal records such as registers and individual patient files. This thesis concludes that the evolution of the Colony's psychiatric community's beliefs around mental illness, philosophies of protective custody and moral treatment within the psychiatric community at the time, the region's laws governing psychiatric institutionalisation, and the larger context of the Cape's socio-political environment at the time converged to create an institution that practiced discrimination on both a macro- and micro-level. This discriminatory framework affected who was admitted, the diagnosis that each person received, the asylum facilities to which they had access, and further, to the odds against their recovery. The implications of this study are relevant in the present day, as the modern South African system of psychiatric institutionalisation, though embedded within a socio-political context of equality and non-discrimination nevertheless appears to suffer from a similarly undemocratic framework of operation.
Keywords: Mental health services -- South Africa -- Cape of Good Hope; Psychiatric hospitals -- South Africa -- History; South Africa -- Race relations -- Social aspects; Mentally ill -- Commitment and detention -- South Africa; Mentally ill -- Abuse of -- South Africa; Mental health policy -- South Africa; Asylums -- South Africa -- Grahamstown; Discrimination in mental health services -- South Africa; Health and race -- South Africa -- History